Coexistence and Development of an Open-Angle Glaucoma in Eyes With Superior Segmental Optic Hypoplasia. Issue 3 (March 2015) - Lee, Hyun Joo; Ozaki, Mineo; Okano, Mayumi; Kee, Changwon
Abstract : Purpose: Superior segmental optic hypoplasia (SSOH) is a congenital disorder that is expected not to progress. This study aimed to determine the prevalence and clinical characteristics of coexistent open-angle glaucoma (OAG) in patients with SSOH. Patients and Methods: We retrospectively reviewed the records of 61 patients diagnosed with SSOH. The estimated prevalence and clinical characteristics of concomitant OAG among patients with SSOH were investigated. Results: Of the 61 patients with SSOH, 12 patients presented with concomitant OAG (mean age, 44.8±19.2 y). Mean follow-up period was 84.9±50.9 months. Five patients (8.2%) were diagnosed with both high-tension glaucoma (HTG) and SSOH; 4 had HTG and SSOH in both the eyes; and the other had HTG only in the eye with SSOH. Seven patients (11.5%) were diagnosed with both normal-tension glaucoma (NTG) and SSOH. Two patients had NTG and SSOH in both eyes and 5 patients had unilateral NTG. The estimated prevalence of OAG in patients with SSOH was 19.7% (95% confidence interval, 9.7%-29.7%). Conclusions: Primary OAG, including HTG and NTG, could develop in eyes with SSOH, regarded as having a nonprogressive visual field defect. The estimated prevalence of OAG, including both NTG and HTG, might be relatively higher in the SSOH patients. Thus, continuous follow-up examinations of patients with SSOH are required.